A Prospective Analysis of the Use of Intraoperative Neuromonitoring for Mapping the S1 Dorsal Root Ganglion Location to Determine Ideal Lead Positioning and Predict Postoperative Programming. Issue 4 (13th April 2020) - Falowski, Steven M.
Abstract : Introduction: The location of the sacral dorsal root ganglion (DRG) is variable and can range from a location in the canal to the foramen. It is therefore imperative to not only ensure a dorsal placement but also map the location of the DRG. Materials and Methods: This is a prospective analysis of the use of intraoperative neuromonitoring (IONM) being utilized in asleep patients to map the location of the S1 DRG with somatosensory evoked potential (SSEP) and electromyogram (EMG) thresholds, as well as comparing this with postoperative programming. These observations were then correlated with the position of the electrode contacts relative to the sacral border. It was performed in a single center with 12 lead placements in eight patients. Results: The IONM demonstrated that EMG thresholds decrease or stay the same as you stimulate more distal on the lead. Sensory signals are generated the majority of the time either proximal or on the sacral border. Postoperative programming correlated with the mapped location of the DRG on IONM, which was either posterior or on the sacral border. There was a single lead in which the IONM confirmed DRG location on the distal contact, which was anterior to the sacral border, and also correlated with postoperative programming. Conclusions: This prospective analysis further demonstrates the utility and accuracy of IONM. The use of DRG IONM is reliable for confirming dorsal placement along the S1 DRG, mapping its position, and guiding postoperative programming. The S1 DRG is located at the border of the foramen and canal in most, but not all cases.